Does online advertising stimulate overconsumption? (Ökologisches Wirtschaften - Fachzeitschrift, 2022)
Alongside its many potentials for sustainable consumption, digitalization also bears considerable risks. Online marketing strategies may increase consumption levels. New results of an experimental study provide multifaceted insights for future research and marketing practice.